A robust control structure enhancing nominal model following scheme for induction servomotor drive - Phanphairoje, S.; Witheephanich, K.; Piyarat, W.; Intajag, S. (My University, 2004)
Motivated by the adaptive model following concept, a robust model following scheme Nominal Model Following Control (NMFC) is developed in this paper. NMFC has three main features: the use of a nominal model of the plant as a reference model, the introduction of a model controller which fulfills the reference tracking requirement and the inclusion of a simple PID correction mechanism which copes with all dynamic deviations of the real plant from its nominal model. Then, a simple robust controller are also designed and augmented with NMFC to reduce the effects of parameter variations and external disturbances further. The proposed control design techniques are employed to show the practicality of the technique for controlling induction servomotor system models. Simulation results illustrate that the desired tracking control performance of the servo drive can be preserved under wide operating range and good load regulating performance can also be obtained.
Keywords: Nominal model following control; PID controller; Plant uncertainty; Robust control